Analysis of BPJS Patient Satisfaction Level of Ralat Road in Hospital Imelda Pekerja Indonesia Medan - Kiki Mirna Ramadhani; Mangatas Silaen; Anto J. Hadi (Science Publication: Journal of Public Health and Nutrition, 2025)
One health service that has a very important role in providing health services to the public is a hospital. Based on the results of interviews that the most frequent complaints they receive are about the system of change set by the BPJS program and the timetable for doctor's services is not as promised. The purpose of this study was to analyze the level of satisfaction of outpatient BPJS patients. The study design used was cross sectional with a total population of 2,056 outpatient BPJS patients and 98 samples were taken by accidental sampling. Data collection methods are primary data and secondary data. Analysis of the data used is multivariate analysis with binary logistic regression test. The results showed that the guarantee has a sig-p value of 0,000 <0.05, empathy has a sig-p value of 0.009 <0.05 and the responsiveness has a sig-p value of 0.001 <0.05. The conclusion in this study there is the effect of assurance, empathy and responsiveness to outpatient BPJS patient satisfaction, while reliability and physical evidence has no influence on BPJS outpatient patient satisfaction. It is hoped that the hospital will improve patient satisfaction for the better, such as giving care to patients who need health services. Keywords : Factor Analysis, Patient Satisfaction Level